2017
DOI: 10.1186/s13102-017-0069-x
|View full text |Cite
|
Sign up to set email alerts
|

Low back pain and FokI (rs2228570) polymorphism of vitamin D receptor in athletes

Abstract: BackgroundLow back pain (LBP) is common in athletes. LBP can be detrimental to athletic performance and health. Factors predisposing to LBP in athletes remain elusive and require further studies. We investigated whether carriage of a specific genotype and/or allele of vitamin D receptor gene (VDR) FokI polymorphism (rs2228570) was a risk factor for LBP in athletes of different sports disciplines.MethodsThis genotype/phenotype association case-control study included 60 Italian athletes (25 females and 35 males;… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 51 publications
0
6
2
Order By: Relevance
“…The 385A allele may be linked to accelerated amygdala reactivity to threat habituation, enhanced learning of how to overcome fear, and diminished anxiety-like behavior. This is crucial for athletes to respond and adapt to unpredictably stressful situations, handle stress more effectively, and increase motivation for performing and competing at a high As for the other two SNPs, in opposition to previous studies on athletic performance [13,27,39], no significant association was identified. However, it should be noted that the present study was not sufficiently powered to detect small effects.…”
Section: Discussioncontrasting
confidence: 64%
“…The 385A allele may be linked to accelerated amygdala reactivity to threat habituation, enhanced learning of how to overcome fear, and diminished anxiety-like behavior. This is crucial for athletes to respond and adapt to unpredictably stressful situations, handle stress more effectively, and increase motivation for performing and competing at a high As for the other two SNPs, in opposition to previous studies on athletic performance [13,27,39], no significant association was identified. However, it should be noted that the present study was not sufficiently powered to detect small effects.…”
Section: Discussioncontrasting
confidence: 64%
“…Odds ratios (ORs) and 95% confidence intervals (CIs) were calculated to determine association of groups with different VDR expression and melanoma characteristics, alleles, genotypes, and combined genotypes. Our study was explorative as no previous investigation determined frequencies of VDR polymorphisms in melanoma patients according to immunohistochemical findings of VDR expression Prior to study enrolment, we evaluated that a number of 70 subjects fitted the 80% power at an alpha level of 0.05 to detect differences between high (above the median) and low VDR expression melanoma groups whether OR value equals 3 or more for a SNP site 47 . Deviation tests from Hardy-Weinberg equilibrium (HWE) were performed using a separate Chi-square distribution for each SNP 29 .…”
Section: Methodsmentioning
confidence: 99%
“…VDR variants studied in the project were rs2228570 C>T, rs731236 T>C, rs1544410 G>A, and rs7975232 A>C. These are the most widely studied variations of the VDR and were previously associated with increased risk of certain diseases. Namely, rs2228570 is associated with chronic kidney disease, low back pain and ovarian cancer (19)(20)(21). Rs731236 was shown to be associated with restless leg syndrome and prostate cancer risk (22,23).…”
Section: Discussionmentioning
confidence: 99%